Developing Learning Tools for Environmental Change Material Using Problem Based Learning Model Based on Local Environmental Conditions in Wonosobo (Universitas Negeri Semarang, 2020)
Environmental change material is a material for Senior High Schools (SMA), especially for class X even / second semester. Preliminary documentation studies showed that Biology learning tools, especially material for environmental change, were not in accordance with the 2013 Curriculum. The purposes of this study are: 1) to test the validity, readability, practicality of the developed learning tools; 2) to test the effectiveness of learning tools that had been developed; 3) describe the characteristics of the learning tools development for environmental change material based on local environmental conditions in Wonosobo. This research is a Research and Development (R&D). The results showed that the learning tools that had been developed were very valid to be used in learning activities of environmental change material. The readability and practicality of learning devices was very good as indicated by the response of the students and the teachers to the learning tools that had been developed. The effectiveness of learning tools showed the results of learning aspects of knowledge achieved classical completeness. The attitude of caring for the environment and the skills of students on the subject of environmental change have reached very good criteria. The characteristics of the learning tools that had been developed provide the examples of environmental damage and lake pollution that occurred in the Dieng Plateau so that learning with PBL model can be done optimally.